Elevated FDG uptake in non-tumorous lung regions does not predict immune checkpoint inhibitor–related pneumonitis in lung cancer patients - Völter, Friederike; Wehlte, Lukas; Resuli, Blerina; Walter, Julia; Daisenberger, Lea; Ingenerf, Maria; Heimer, Maurice; Brendel, Matthias; Sheikh, Gabriel T.; Unterrainer, Lena M.; Kauffmann-Guerrero, Diego; Pfluger, Thomas; et al. (Frontiers in Oncology, 2025)
BackgroundPredictors for checkpoint inhibitor-related pneumonitis (cinrPneumonitis) are desperately needed. This study aimed to investigate the pretreatment standardized uptake value (SUV) on [18F]FDG-PET/CT of non-tumorous lung tissue as a predictive imaging marker for the development of cinrPneumonitis in 239 patients with lung cancer.MethodsAll patients with lung cancer receiving [18F]Fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) prior to immune checkpoint inhibitor (ICI) therapy were included and retrospectively analyzed. Pretreatment SUVMEAN, SUVMAX, SUV95, SUV normalized by lean body mass (SULMEAN, SULMAX) and clinical variables were compared for patients with and without cinrPneumonitis. Logistic regression analyses were performed to identify the predictive value of pretreatment SUV for the development of cinrPneumonitis.ResultsA total of 239 patients were included, of whom 41 (17.2%) developed cinrPneumonitis. The pretreatment radioligand uptake (SUVMEAN, SUVMAX, SUV95, SULMEAN and SULMAX) was not significantly elevated in patients who developed cinrPneumonitis. Logistic regression using sex, age, body mass index and chronic obstructive pulmonary disease as covariables additionally showed no significant association between pretreatment radioligand uptake and the risk of cinrPneumonitis. However, an increased likelihood of developing cinrPneumonitis (relative risk = 1.979; p = 0.027) was shown in patients who received thoracic radiation during ICI therapy.ConclusionThis is the largest study on the association of pretreatment radioligand uptake of the non-tumorous lung and the risk of a cinrPneumonitis. Our results showed no significant association between elevated pretreatment radioligand uptake of non-tumorous lung tissue on FDG-PET/CT and the development of cinrPneumonitis.